Overview Of Diarrhea Incidents In Toddlers In The Work Area Wera Public Health Center, Bima District - Faturahmah, Erni (Jurnal EduHealth, 2024)
Less than 1.7 billion per year, digestive system health problems (diarrhea) are one of the causes of death for children. In the province of NTB in 2023, the number of cases of diarrhea in toddlers ranks second after East Lombok district with a total of 7,974 cases of diarrhea in toddlers. Research method, type of quantitative descriptive research. Retrospective research design . Single variable is the description of the incidence of diarrhea in toddlers. The research location was carried out in the working area of the Wera Health Center, Bima Regency, NTB in 2023. The population and sample were all toddlers who experienced diarrhea, the sampling technique used was total sampling . The research instrument used was a checklist sheet . Furthermore, it was analyzed using univariate analysis. The results of the study, the highest incidence of diarrhea was in 2023 with a total of 205 (38.9%) cases of toddlers experiencing diarrhea. Characteristics of the age of toddlers, most of whom were in the 1 year age group, namely 63 (30.7%). Most cases of diarrhea in toddlers occurred in Sangiang village with 28 (13.7%) toddlers who had experienced diarrhea. The conclusion is that the largest age group is 1 year old and the area with the most diarrhea cases is in Sangiang village. Suggestions are that socialization of prevention and early handling ofdiarrhea in the Wera Health Center work area be improved.